A BI-REGIONAL INPUT-OUTPUT MODEL FOR GALICIA AND THE REST OF SPAIN: ESTIMATING SPILLOVER AND FEEDBACK EFFECTS OF TOURISM. - Andre Carrascal-Incera (European Regional Science Association (ERSA), 2011)
The main particularity of Tourism is to be defined from the demand side, instead from the supply side like the other economic activities. For this reason, Tourism impact studies are usually performed with demand models based on input output (IO) methodology. Moreover, these types of models allow us to identify the direct and indirect effects of changes in final demand. Originally, the applications of the classic Leontief model were undertaken at national level, but the important disparities in regional specialization resulted in the development of input-output tables at more disaggregated level. Nevertheless, one-region models do not recognize the interdependencies between regions, i.e. each region appears isolated from the others. This is a really hard assumption in the regional analysis since exchange of workers and trade of goods with the rest of the country is much important at this level. Therefore, the aim of this paper is to compare the results obtained with the classic demand model with a two-region model. Using the bi-regional model, it is possible to measure the existence and significance of outflows or "leakages" and inflows or "gains" in the production process, whether from trade or use of non-resident workers. For practical purposes, we estimate the economic impact of Tourism for a Spanish region, Galicia. In this way, we can consider the peculiarities of its productive structure and its relation with the Rest of Spain taking into account the spillover (outflows) and the feedback effects (inflows).
Keywords: 330